Machinations:: High-Resolution Sounding Using Ground-Probing Radar - Davis, J.; Annan, A. (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1986)
Summary Ground-probing radar is a high-resolution sounding technique that can map bedrock topography and soil strata. High-resolution sub-surface mapping is frequently required by geologists, geotechnical engineers and hydrogeologists for defining buried bedrock topography and soil stratigraphy. Current ground-probing radar systems can sound to 20 m depth in resistive geological materials. New sounders such as the EKKOII electromagnetic profiler developed by Á-Cubed Inc. are more than doubling this depth. The principles of the radar method and three field examples are presented to show the potential of radar soundings and the versatility of the method. As with any geophysical technique, the radar soundings are most effective when used in conjunction with other techniques especially borehole logging.